Evaluations in the English-Speaking Commonwealth Caribbean Region: Lessons From the Field. (June 2020) - Persaud, Nadini; Dagher, Ruby
This article shares lessons from the field with program evaluations in the English-Speaking Commonwealth Caribbean (ESCC) region. The research highlighted that the challenges faced by evaluators working in the ESCC are quite similar to those experienced by evaluators elsewhere. However, the findings note the impact of the region's colonial past and the developing–developed nexus on the ESCC people's sense of pride and their desire to demonstrate the level of their expertise and its equivalence to the expertise associated with people in North America and Europe. These factors seem to contribute to an important undertone for evaluations in the region and for the challenges that evaluators face, including the limited culture of evaluation as well as the availability and quality of data.